2019
DOI: 10.1029/2018wr023760
|View full text |Cite
|
Sign up to set email alerts
|

Lithologically Controlled Subsurface Critical Zone Thickness and Water Storage Capacity Determine Regional Plant Community Composition

Abstract: Explanations for distinct adjacent ecosystems that extend across hilly landscapes typically point to differences in climate or land use. Here we document—within a similar climate—how contrasting regional plant communities correlate with distinct underlying lithology and reveal how differences in water storage capacity in the critical zone (CZ) explain this relationship. We present observations of subsurface CZ structure and groundwater dynamics from deep boreholes and quantify catchment‐wide dynamic water stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
185
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 120 publications
4
185
0
Order By: Relevance
“…By coupling our understanding of the subsurface hydrology of our sites (Dralle et. al, 2016; Druhan et al, ; Hahm et al, ; Kim et al, ; Link et al, ; Oshun et al, ; Rempe & Dietrich, ; Rempe et al, ; Salve et al, ) with wetted channel observations at the beginning and end of the summer dry season, our study demonstrates the connection between critical zone structure and the extent and duration of wetted channels.…”
Section: Introductionsupporting
confidence: 64%
“…By coupling our understanding of the subsurface hydrology of our sites (Dralle et. al, 2016; Druhan et al, ; Hahm et al, ; Kim et al, ; Link et al, ; Oshun et al, ; Rempe & Dietrich, ; Rempe et al, ; Salve et al, ) with wetted channel observations at the beginning and end of the summer dry season, our study demonstrates the connection between critical zone structure and the extent and duration of wetted channels.…”
Section: Introductionsupporting
confidence: 64%
“…We rejected these explanations because (i) there are consistent, large seasonal swings in EVI at storage-capacity-limited sites with diverse plant communities (see Figure 11 of Hahm et al, 2019), and (ii) greenness across a wide range of plant communities has been shown to be significantly correlated with water storage (Yang et al, 2014). We rejected these explanations because (i) there are consistent, large seasonal swings in EVI at storage-capacity-limited sites with diverse plant communities (see Figure 11 of Hahm et al, 2019), and (ii) greenness across a wide range of plant communities has been shown to be significantly correlated with water storage (Yang et al, 2014).…”
Section: The Decoupling Of Summer Plant Greenness From Winter Precipimentioning
confidence: 99%
“…The subsurface CZ at Dry Creek consists of a shallow soil (~40 cm) developed on a relatively thin saprolite and weathered bedrock zone that transitions to low porosity, low conductivity fresh parent material at only~2-m depth (Dralle et al, 2018;Hahm et al, 2019;Lovill et al, 2018). The subsurface CZ at Dry Creek consists of a shallow soil (~40 cm) developed on a relatively thin saprolite and weathered bedrock zone that transitions to low porosity, low conductivity fresh parent material at only~2-m depth (Dralle et al, 2018;Hahm et al, 2019;Lovill et al, 2018).…”
Section: Observations and Hydrologic Mechanisms Of Storage-capacity-lmentioning
confidence: 99%
See 2 more Smart Citations